Women’s Role in Agriculture - Ahmadi Begum (International Journal of Modern Agriculture, 2021)
Among the various growing sectors, agriculture is one of the most important sector. In other way agriculture sector is the growing infusion of science and technology. In case of developing countries such as India, employ and hired women in agricultures but do not hired labours for rural women. Here in the present paper role of women in agriculture discussed wherein various important factors in agriculture are discussed. The different factors such as agriculture linked with economic growth, women contribution in agricultural operations performed by the labourers, energy and time distribution by rural women, different tasks women in agriculture, problem faced by women in agriculture, ratio of women in agriculture in percentage and their safety and health issues etc. The new policies are not plummeting the women labour ignorance as an integral part of agriculture sector. For the future scope different other factors can be discussed with agricultures such as dependence of agricultures in economics.